Fluorescence Lifetime Imaging for Quantification of Targeted Drug Delivery in Varying Tumor Microenvironments - Amit Verma; Vikas Pandey; Catherine Sherry; Taylor Humphrey; Christopher James; Kailie Matteson; Jason T. Smith; Alena Rudkouskaya; Xavier Intes; Margarida Barroso (Advanced Science)
Abstract Trastuzumab (TZM) is a monoclonal antibody that targets the human epidermal growth factor receptor 2 (HER2) and is clinically used for the treatment of HER2‐positive breast tumors. However, the tumor microenvironment can limit the access of TZM to the HER2 targets across the whole tumor and thereby compromising TZM's therapeutic efficacy. An imaging methodology that can non‐invasively quantify the binding of TZM‐HER2, which is required for therapeutic action, and distribution within tumors with varying tumor microenvironments is much needed. Near‐infrared (NIR) fluorescence lifetime (FLI) Forster Resonance Energy Transfer (FRET) is performed to measure TZM‐HER2 binding, using in vitro microscopy and in vivo widefield macroscopy, in HER2 overexpressing breast and ovarian cancer cells and tumor xenografts, respectively. Immunohistochemistry is used to validate in vivo imaging results. NIR FLI FRET in vitro microscopy data show variations in intracellular distribution of bound TZM in HER2‐positive breast AU565 and AU565 tumor‐passaged XTM cell lines in comparison to SKOV‐3 ovarian cancer cells. Macroscopy FLI (MFLI) FRET in vivo imaging data show that SKOV‐3 tumors display reduced TZM binding compared to AU565 and XTM tumors, as validated by ex vivo immunohistochemistry. Moreover, AU565/XTM and SKOV‐3 tumor xenografts display different amounts and distributions of TME components, such as collagen and vascularity. Therefore, these results suggest that SKOV‐3 tumors are refractory to TZM delivery due to their disrupted vasculature and increased collagen content. The study demonstrates that FLI is a powerful analytical tool to monitor the delivery of antibodydrugs both in cell cultures and in vivo live systems. Especially, MFLI FRET is a unique imaging modality that can directly quantify target engagement with the potential to elucidate the role of the TME in drug delivery efficacy in intact live tumor xenografts.